IP-Traffic Theory and Performance - Grimm, Christian; Schlüchtermann, Georg; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book presents different approaches in IP traffic theory and classifies them, especially towards applications in the Internet. It comprises the state of the art in this area, which is currently presented only by numerous research papers and overview articles. The book provides an ideal starting point for detailed studies of traffic analysis in IP networks. It gives the reader the possibility to judge on different models and to select the appropriate for his individual needs in applications. The mathematical toolbox for this is kept as low as low as possible – the authors build a bridge between abstract representation of mathematical tools and applications. This, in turn, is certainly the most interesting topic for experts planning large data networks as well as practitioners and researchers working in this area The book also serves as useful reference for lecturers and students at universities.
to IP Traffic -- Classical Traffic Theory -- Mathematical Modeling of IP-based Traffic -- Statistical Estimators -- Performance of IP: Waiting Queues and Optimization.
Keywords: Electrical engineering; Computer communication systems; Electronics; Microelectronics; Information theory; Communications Engineering, Networks; Computer Communication Networks; Electronics and Microelectronics, Instrumentation; Information and Communication, Circuits